Atmospheric moisture tracking with WAM2layers v3 - P. Kalverla; I. Benedict; C. Weijenborg; R. J. van der Ent (Geoscientific Model Development, 2025)
This paper documents the atmospheric-moisture-tracking model WAM2layers v3 (Water Accounting Model – 2 layers, version 3). WAM2layers may be used to gain an understanding of atmospheric dynamics and to study rainfall patterns and extremes by mapping their sources or sinks, often in the context of climate and land-use changes. To this end, WAM2layers solves a prognostic equation for tagged moisture in gridded atmospheric datasets such as reanalysis data or climate model output. WAM2layers can be used in forward mode, to determine where evaporated water eventually precipitates, or in backward mode, to determine where precipitation originally evaporated.